2020
DOI: 10.1111/rec.13322
|View full text |Cite
|
Sign up to set email alerts
|

Considering the use of subadult and juvenile mussels for mussel reef restoration

Abstract: Widespread resource extraction and habitat degradation have severely reduced functionally important subtidal mussel reefs globally. While methods for restoring oyster reefs are becoming increasingly well-established, the development of techniques for the effective restoration of mussel reefs remain in their infancy and face biological and logistical challenges. This study investigated the potential use of subadult and juvenile green-lipped mussels (Perna canaliculus) for mussel reef restoration with the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Previous work found that loose, unprotected subadult and juvenile mussels disappear within 1 week of being placed at experimental sites (Alder et al 2020). To improve initial postdeployment survival, the mussels in this study were provided a clumping period prior to deployment.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous work found that loose, unprotected subadult and juvenile mussels disappear within 1 week of being placed at experimental sites (Alder et al 2020). To improve initial postdeployment survival, the mussels in this study were provided a clumping period prior to deployment.…”
Section: Methodsmentioning
confidence: 95%
“…The restoration of biogenic habitat depends on careful consideration of larval, seed, and adult stock sources (Schulte et al 2009; Fitzsimons et al 2019). For restoration that relies on translocations of populations from aquaculture, careful stock selection that accounts for growth conditions and size may improve survival and restoration efficiency (Alder et al 2020) while avoiding the use of costly engineering interventions (Capelle et al 2019; Schotanus et al 2020 a , 2020 b ). In this study, variations in post‐translocation survival were closely related to stock source and differences observed in the formation of protective clumps as explained by two aspects of clumping behavior (P:A ratio, D ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations